Proceedings of the Symposium on Malaysian Gas Industry '90, 18-19 September 1990, Petronas Management Training Institute (PERMATA) - Symposium on Malaysian Gas Industry (1990 : Bangi, Selangor); Universiti Teknologi Malaysia. Fakulti Kejuruteraan Kimia dan Kejuruteraan Sumber Asli; Petronas Management Training Institute (PERMATA) (Bangi : PERMATA, 1990)
Development of the Malaysian gas industry/ Hashim Salleh -- The transAsean gasline/ Marcello Colitti -- Economic prospects of domestic gas utilisation in Asean energy markets/ Prof. Madya De. Wan Leong Fee -- Overview of field handling of natural gas/ Nadeem Shaik -- Peninsular gas utilisation project - Stage II (PGU II) System II/ K. Yamaji ...[et al] -- Dry seal and magnetic bearing installation and commissioning/ P.T. Gallagher, D.A. Pragnel -- Development in fiscal metering of NG and MLNG/ Tan Ah Ee -- The commercial utilisation of associated gas/ Dr. Deutsch -- Pipeline engineering in an engineering, procurement and construction (EPC) environment/ Les Gray -- Gas and petrochemical development in Malaysia and bisuness opportunities/ Shamsuddin Basri -- Supplying natural gas to the customer/ David Kemp, J.C. Conway -- Natural gas for vehicles : an innovative NG application/ J.R. Higginson -- Finance/ Aladdin Hj. Mohd. Lip -- Polisi dan undang-undang industri petroleum di Malaysia/ Y.M. Tengku Alauddin Majid -- Rules and regulations on safety in gas industry/ Zakaria Nanyan -- Investment tax incentives for gas industry/ Lee Sum Tung -- Environmental impact assessment requirements and procedure in Malaysia : natural gas utilisation in power generation/ Noor Alshurdin Md. Salleh ...[et al] -- Persiapan latihan menyambut kedatangan era gas di Malaysia/ Kandan Saikon -- The role of UTM in providing gas engineering education/ Mohd Norani Abd. Rahman ...[et al] -- Blogas : an alternative gas/ Mohd. Zaki Kamsah